2003
DOI: 10.1055/s-2003-41285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leptin on Hypothalamic Release of GnRH and Neurotransmitter Amino Acids During Sexual Maturation in Female Rats

Abstract: The purpose of the present study was to analyse the effect of leptin treatment on the hypothalamic release of GnRH, GABA, and the excitatory amino acids (EAA), aspartate (ASP) and glutamate (GLU) involved in NMDA neurotransmission in prepubertal (15 day old) and peripubertal (30 day old) female rats. The animals were treated with a single dose of leptin (30 microg/kg i.p.) and sacrificed 60 min later. Hypothalamic samples were incubated in Earle's medium; GnRH was determined by RIA and GLU, ASP and GABA by HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Besides its central effects, it has been demonstrated that ghrelin can also modulate the reproductive function through its actions on the pituitary and gonads [45]. Ghrelin exerts a negative effect on GnRH neurons [45], whereas leptin regulate and increases GnRH secretion [119]. Central ghrelin injection to ovariectomized rats suppress LH pulse frequency [51].…”
Section: Ghrelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its central effects, it has been demonstrated that ghrelin can also modulate the reproductive function through its actions on the pituitary and gonads [45]. Ghrelin exerts a negative effect on GnRH neurons [45], whereas leptin regulate and increases GnRH secretion [119]. Central ghrelin injection to ovariectomized rats suppress LH pulse frequency [51].…”
Section: Ghrelinmentioning
confidence: 99%
“…[45,119] Although neuron-specific insulin receptorknockout (NIRKO) mice exhibit hypogonadism selective ablation of IR on GnRH neurons does not affect the fertility.…”
Section: Study Observations Interpretation Of Data Published Studiesmentioning
confidence: 99%
“…A requirement for such a factor is that mutations in its gene, whether in human and/or mouse models, must result in infertility or significant reproductive dysfunction. Leptin fulfills both of these requirements as shown by the infertility of leptin-deficient mice and humans and their leptin mediated rescue (Chehab et al 1996; Farooqi et al 1999; Gibson, et al 2004) as well as its indirect stimulation of GnRH (Nagatani, et al 1998; Reynoso, et al 2003) and the potentiation of LH release from pituitary gonadotropes in the presence of GnRH (Avelino-Cruz, et al 2009). Leptin also appears to exert GnRH independent effects on the reproductive system as shown by its ability to induce ovulation in GnRH deficient mice (Barkan, et al 2005), an intriguing but interesting finding.…”
Section: I- Leptin In Pubertymentioning
confidence: 99%
“…It has been suggested that an increase in serum leptin is associated with the onset of puberty. In previous studies we have demonstrated that leptin administration increases Gn-RH release in female rats during sexual maturation [10][11][12] . Leptin release is under neural control; the sympathetic nervous system exerts an inhibitory tonic effect on leptin release mediated predominantly by ␣ -adrenergic and, to a lesser extent, by ␤ -adrenergic receptors that are still present and may be augmented by LPS [13] .…”
mentioning
confidence: 99%